Penafsiran Bakri Syahid Tentang Kepemimpinan dalam Al-Huda Tafsir Qur'an Basa Jawi - Maya, Ria Tri; Badruzaman, Abad; Noorhidayati, Salamah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Leadership is important because it becomes the milestone of a community. About this leadership, not only found in the Qur’an but also found in Javanese philosophy, considering that Javanese philosophy is a teaching that is full of deep meaning. There are several figures who try to combine the Qur’an with Javanese philosophy, Bakri Syahid is one of them. In his work Al-Huda Tafsir Qur’an Basa Jawi it uses subtle Javanese language, he combines the Qur’an with Javanese philosophy. The conception of leadership according to Bakri Syahid in Tafsir Al-Huda there are three, namely socialist, mandate, and religious. When interpreting verses from the Qur’an Bakri Syahid also includes elements of Javanese culture. The influence of Javanese culture in Tafsir Al-Huda can be seen in its interpretation that combines Islamic teachings with Javanese culture, such as the use Javanese philosophical concepts contained in Serat Wulang Reh.